Restriction of T cell receptor Vβ repertoire in melanoma metastasis responding to immunotherapy - Möhler, Thomas; Willhauck-Fleckenstein, Martina; Scheibenbogen, Carmen; Pawlita, Michael; Bludau, Hans-Bernd; Brossart, Peter; Hunstein, Werner; Keilholz, Ulrich (Melanoma research, 1995)
Restriction of the T cell receptor repertoire suggesting ongoing specific immune mechanisms has recently been described in melanoma tissue by several groups of investigators. The functional relevance for immunotherapy of melanoma, however, has not been established. We studied the T cell receptor repertoire in two melanoma metastases of a patient with a mixed response to immunotherapy. Expression of T cell receptor Vβ regions was determined by subgroup-specific semiquantitative RNA polymerase chain reaction (PCR). In the regressing skin lesion a restricted expression of the T cell receptor repertoire and overexpression of three Vβ subgroup genes was found; no restriction was present in the simultaneously progressing skin lesion of the same patient, compared with peripheral blood lymphocytes. Comparison of T cell receptor vβ gene expression in two metastatic lesions of a patient with simultaneously growing skin metastases, who did not receive immunotherapy, revealed only minor differences. These observations show for the first time an association between restricted T cell receptor repertoire and responsiveness of melanoma to immunotherapy and suggest a role of T cells using the overexpressed Vβ genes for the cytokine-induced tumour regression.